2020
DOI: 10.1177/2192568220938024
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Lumbar Interbody Fusion Procedures for Degenerative Disc Disease: A Systematic Review With Network Meta-Analysis of Prospective Studies

Abstract: Study Design: A network meta-analysis. Objectives: Lumbar degenerative disc disease (LDDD) is an important issue in aging population, for which lumbar interbody fusion (LIF) is a feasible management in cases refractory to conservative therapy. There are various techniques available to perform LIF, including posterior (PLIF), transforaminal (TLIF), and anterior (ALIF) approaches. However, the comparative safety profile of these procedures remains controversial. Our study aimed to evaluate comparative adverse ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
(98 reference statements)
3
11
0
Order By: Relevance
“…However, our result TLIF seems to be safer than PLIF and ALIF in neural, spinal, and vascular events. Those findings were similar to a previous study by Chi et al ( 9 ). Nonetheless, Yavin et al demonstrated more complications in the fusion group compared to the non-fusion group ( 38 ).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…However, our result TLIF seems to be safer than PLIF and ALIF in neural, spinal, and vascular events. Those findings were similar to a previous study by Chi et al ( 9 ). Nonetheless, Yavin et al demonstrated more complications in the fusion group compared to the non-fusion group ( 38 ).…”
Section: Discussionsupporting
confidence: 93%
“…The TLIF has a slightly low fusion rate at 1 year and remains unchanged at 2 years. Further study on potential multifactorial factors supports the fusion ( 9 ).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations